Comparative Study of Ag Nanostructures: Molecular Simulations, Electrochemical Behavior, and Antibacterial Effect. (30th November 2016) - Ruíz-Baltazar, Álvaro de Jesús; Reyes-López, Simón Yobanny; Larrañaga, D.; Pérez, R.
Abstract : Nanoparticles of Ag with different sizes and structures were obtained and studied. Two methods for reductions of Ag ions were employed, chemical reduction by sodium borohydride and ethylene glycol. Cuboctahedral and icosahedral structures were obtained. Molecular simulations were carried out in order to evaluate the reactivity of both structures. On the other hand, the electrochemical activity and antibacterial effect ( E. coli ) of the cuboctahedral and icosahedral structures were measured experimentally. The results obtained by molecular simulation, cyclic voltammetry, and antibacterial effect were compared and discussed in this work.